Comparison of Fat Graft in Post-Burn Scars versus Platelet-Rich Plasma Regarding Scar Quality and Healing: Platelet-Rich Plasma and Fat Graft in Post-Burn Scar Treatment - Nasrullah, Muhammad; Amin, Muhammad; Fatima, Samia; Imdad, Sana; Allavi, Hirra Rehman; Imran, Muhammad; Aftab, Aiza Latif (Pakistan Journal of Health Sciences, 2024)
Post-burn scars occur when burns damage the skin leading inevitable injury. Various techniques are applied for treatments and reduction so f these scares. Objective: To compare the effect of Platelet Rich Plasma (PRP) and fat graft in post-burn scars on the outcome of the healing process and quality of chronic wounds. Methods: One hundred cases were equally divided in group I (platelet-rich plasma) and group II (fat graft), age between 20-60 years were enrolled. The patients were those who were having post traumatic or and post burn chronic wounds which were within the duration of ≥3 months. A 5cc blood was withdrawn from each patient. Fat graft and platelet rich plasma were prepared, applied and compared for up to 12 weeks for their wound size, healing rate and scar quality. Results: There was no difference win age or gender within groups with a mean age of 43.46 and 44.36 years in group I and Group I. The comparative analysis within the original wound size and decrease in it within the 4 weeks’ time followed by 12 weeks’ time presented significant variance with both procedures bringing sufficient minimizing in the size, however a slight better result was presented in group II in comparison with Group I. Average healing rate was higher in group II than group I. Conclusions: Both procedures are efficient in terms of scar quality and healing of post burn scar. However, within the two groups the fat graft is more efficient and reliable with high healing time and rate.